Prognostic Value of Trop‐2 Expression in Nonmetastatic Triple‐Negative Breast Cancer and Correlation With Emerging Biomarkers - William Jacot; Marie‐Christine Chateau; Simon Thezenas; Séverine Guiu; Nelly Firmin; Virginie Lafont; Gwendal Lazennec; Charles Theillet; Florence Boissière‐Michot (Cancer Medicine)
ABSTRACT Introduction Triple‐Negative Breast Cancer (TNBC) is an aggressive breast cancer subtype, in which targeting the Trophoblast cell‐surface antigen‐2 (Trop‐2), using antibody‐drug conjugates (ADC), results in significant clinical improvement. However, clinicopathological correlations with Trop‐2 protein expression levels remain limited in TNBC patients. Methods Here we assessed by immunohistochemistry (IHC) using the mouse monoclonal anti‐Trop‐2 antibody (Enzo, Cat. ENZ‐ABS380) cell membrane Trop‐2 expression levels and classified them in 3 H‐Score classes, low (< 100), moderate (100–200), and strong (> 200). We also evaluated potential associations with clinicopathological variables including basal‐like and molecular apocrine phenotypes, immune infiltrate characteristics, PTEN and PIK3CA alterations in a large retrospective series of 228 nonmetastatic TNBC patients. Results Trop‐2 expression was evaluated as low, moderate and strong in 12.3%, 28.9%, and 58.8% of the cases respectively. Only 3 tumors showed no Trop‐2 expression. Interestingly, Trop‐2 expression was not associated with classical breast cancer clinicopathological variables, HER2 levels or molecular subtype, neither did we observe an association with relapse‐free survival. Only a marginal association with pT1 tumors was observed, which tended to express increased levels of Trop‐2 protein. In order to determine possible fluctuations of Trop‐2 protein expression levels during the course of the disease, we studied a second independent cohort of 18 TNBC comprised of serial tissue samples (diagnostic biopsies, surgical resection specimens and corresponding patients‐derived xenografts (PDX)). Trop‐2 levels remained globally stable between cognate tumor samples with only one exception corresponding to a Trop‐2‐negative tumor giving rise to a Trop‐2‐positive PDX. Conclusions As Trop‐2 expression appears nearly constant and independent of classical TNBC variables and outcome, association of anti‐Trop‐2 therapies with other targeted therapies can be evaluated without reducing the population in specific TNBC subgroups.